Analisis Strategi Manajemen Biaya di PT Unilever Indonesia dalam Mengoptimalkan Efisiensi Operasional dan Meningkatkan Profitabilitas - Astika, Yunanik; Sholihah, Nikmatus; Retnowati, Eka; Fitria, Indah Ayu; Maulidia, Maulidia; Sofiyah, Sofiyah (Reviu Akuntansi, Manajemen, dan Bisnis, 2024)
Purpose: This research aims to analyze the cost management strategies implemented by PT Unilever Indonesia to optimize operational efficiency and enhance profitability within the competitive Fast Moving Consumer Goods (FMCG) sector. Methodology: This study employs a quantitative literature review, analyzing secondary data sourced from annual reports, journal articles, and company publications to identify patterns in PT Unilever Indonesia’s cost management practices. Results: The study finds that PT Unilever Indonesia’s cost management strategies, including supply chain optimization and technological adoption, have a positive correlation with operational efficiency and profitability. Conclusions: Cost management strategies implemented by the company have proven effective in achieving goals. Strategies that involve identifying patterns and trends over a period of time, with a focus on operational efficiency and improving financial performance. Limitations: This study relies on secondary data, which may limit insights into qualitative factors such as organizational culture that impact cost management effectiveness. Contribution: This research provides insights into effective cost management strategies for the FMCG sector, offering value to industry practitioners and academics focused on operational efficiency and profitability enhancement.